Direct Inkjet Printing of Dielectric Ceramic/Polymer Composite Thick Films†. Issue 9 (21st January 2015) - Mikolajek, Morten; Friederich, Andreas; Kohler, Christian; Rosen, Melanie; Rathjen, Andreas; Krüger, Klaus; Binder, Joachim R.
<x xml:space="preserve">Abstract</x> This article describes the preparation of composite thick films via inkjet printing in one process step. A novel ceramic/polymer ink is developed, suitable for the fabrication of homogeneous dielectric composite thick films. Therefore, a barium strontium titanate (BST) dispersion is prepared and combined with a highly loaded polymer solution afterwards. Ba0.6Sr0.4TiO3 is synthesized by a sol‐gel method and dispersed in butyl diglycol using a stirred media mill. A poly(methyl methacrylate) (PMMA) solution is prepared in butanone and mixed with the BST dispersion to obtain an ink with a 50:50 volume ratio of BST and PMMA. The ink characteristics and printability are investigated, in particular the drying behavior of the ink at different temperatures and the morphology of the composite thick films. The drying behavior of low viscosity particle suspensions is often influenced by the coffee stain effect. However, for the developed composite ink no coffee stain effect is observed and homogeneous composite thick films are achieved. Afterwards, all‐inkjet‐printed capacitors are fabricated, using the developed composite ink. Finally, the relative permittivity εr and loss tangent tan δ of the composite thick films are determined.